Students' perceptions of students', parental and peers' mathematics anxiety: effects on mathematics achievement - Tan, Fong Min (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This study aimed to identify the relationships between students' perceptions towards mathematics anxiety, students' perceptions of parental mathematics anxiety, students' perceptions of peers' mathematics anxiety and students' mathematics achievement. Besides, this study also aimed to determine differences- in students' perceptions towards mathematics anxiety, students' perceptions of parental mathematics anxiety, students' perceptions of peers' mathematics anxiety and students' mathematics achievement based on race. The respondents were three hundred Form Four students from four secondary schools in Kuching and two secondary schools in Sibu. In this study, the instrument used was the 10 items Mathematics Anxiety Rating Scale Revised(MARS-R, Plake & Parker, 1982, cited in He, 2007). The mathematics scores of the three hundred Form Four students represented the measure of mathematics achievement in this study. In particular, the Pearson product-moment correlations were used to determine the relationships between students' perceptions towards mathematics anxiety, students' perceptions of parental mathematics anxiety, students' perceptions of peers' mathematics anxiety and students' mathematics achievement. One-Way Analysis of Variance (ANOVA) tests were used to determine the differences in students' perceptions towards mathematics anxiety, students 'perceptions of parental mathematics anxiety, students' perceptions of peers' mathematics anxiety and students' mathematics achievement based on race. The findings of this present study indicated that there were negative relationships between students' perceptions towards mathematics anxiety, students' perceptions of parental mathematics anxiety, students' perceptions of peers' mathematics anxiety and students' mathematics achievement. Besides, the study also shown that there were significant differences in students' perceptions towards mathematics anxiety, students' perceptions of parental mathematics anxiety, students' perceptions of peers' mathematics anxiety and students' mathematics achievement based on race.